Perbandingan Kredit Pemilikan Rumah Pada BANK Konvensional Dengan Pembiayaan Kepemilikan Rumah Pada BANK Syariah - Rusandry Rusandry; Agatha Christy Situru; Hijrasil Hijrasil; Syahrial Maulana (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2024)
In this study discusses the differences between the provision of mortgageson conventional bank financing of home ownership inIslamic banks. The result so fthis study indicate a difference in the systems used inconventional banks to Islamic banks.The most fundamental differenceis the system of interestare used inconventional banking and losss haring principle in Islamic banking. With the system of interestrateisset to change at any time in accordance with bank policies, where as if you use the principle of profit sharing and loss margin can not be changed because it is in conformity with the murabaha contract.